Review on cyber-security for optimized and smart irrigation systems - Wid Badee Abdulaziz; Muayad Sadik Croock (Universitas Ahmad Dahlan, 2023)
It is well known that the resources in agriculture are considered the most important factors for success. Therefore, numerous researchers are involved in the field of managing these resources, particularly water and consumed power. Moreover, the security side of these resources is considered, particularly the cyber-attacks. In this project, an optimized resource management method is proposed for allocating the available resources in a smart on-demand way. The proposed method is applied for dripped and sprinkler irrigation systems for managing the available water and generated power. In addition, an optimization method is utilized to obtain reliable solutions for managing the adopted resources. This method adopts a cyber security algorithm for preventing any possible attack. Wireless sensor network (WSN) is used as a reading source, in which the underlying area is covered well, since using sensors in irrigation systems is cost-effective that ensures on-demand irrigation process to save water and power resources. This network is supported by the fault tolerance method to increase availability.